Environmentally sound technology for efficient water application in integral sustainable urban development: Fraccionamiento Terralta area in Gadalajara, Jalisco, Mexico - Córdova Canela, Fernando; de Hoyos Martínez, Jesús Enrique; Velázquez Angulo, Gilberto (UNIVERSIDAD ANTONIO NARIÑO, 2017)
In this paper, we propose the construction of the efficacy evaluation model; environmentally sound technology applied to the first Integrally Sustainable Urban Development (DUIS) located in the Metropolitan Area of Guadalajara, in order to analyze the environmentally sound technology hydraulic infrastructure alternatives which can be recommended in this project. /e model includes categories such as environment, technology, urban and citizen participation, and it’s proposed as an input to urban planning, which allows the visualization of how the environmentally sound water technologies could be implanted in the DUIS.